Idiopathic portal hypertension: Natural history and long‐term outcome. Issue 6 (28th February 2014) - Siramolpiwat, Sith; Seijo, Susana; Miquel, Rosa; Berzigotti, Annalisa; Garcia‐Criado, Angeles; Darnell, Anna; Turon, Fanny; Hernandez‐Gea, Virginia; Bosch, Jaume; Garcia‐Pagán, Juan Carlos
<x xml:space="preserve">Abstract</x> Idiopathic portal hypertension (IPH) is a rare cause of intrahepatic portal hypertension. Data on natural history and prognosis of IPH are limited. We sought to describe the complications and long‐tem outcome of IPH by retrospectively studying 69 biopsy‐proven cases of IPH. Mean duration of follow‐up was 6.7 ± 4.6 years. All patients had evidence of portal hypertension (PH) at diagnosis, and 42% were symptomatic. Variceal bleeding (VB) was the most common manifestation. In those without bleeding at diagnosis, 74% had varices at first endoscopy. In those with large varices, the 1‐year probability of first bleeding despite primary prophylaxis was 9%. The 1‐year probability of rebleeding was 22%. Ascites and hepatic encephalopathy was documented in 26% and 7% of patients, respectively, at least once during the clinical course. The 1‐year probability of developing portal vein thrombosis (PVT) was 9%, and 53% of patients receiving anticoagulation achieved recanalization. Human immunodeficiency virus (HIV) infection and VB at diagnosis were the independent predictors of PVT. Seven patients died (6 as a result of an IPH‐related cause) and 2 were transplanted. Probability of liver transplantation–free survival was 82% at 10 years. Presence of a severe associated disorder and ascites as a presenting symptom were associated with poor survival. Conclusion: Variceal bleeding is a major complication of IPH. Using, in IPH patients, the same management approach for PH as in cirrhosis is safe and maintains a low incidence of first bleeding and rebleeding in IPH patients. PVT is a frequent complication, particularly in those with HIV infection. Despite several complications, overall survival of patients with IPH is considerably good. (Hepatology 2014;59:2276–2285)